Spectrum sensing algorithm using ANN in cognitive radio - Esam Kamal, Ayoub; B. Salih, Arshad; Najdet Nasret Coran, Ali (International Journal of Engineering and Technology, 2019)
Studies of cognitive radio context raised major challenges about assigning SUs into licensed bands. Such challenges stand for time more likely, when the SU begins transmission and when it terminates the transmission? Asking this question implies that SU may limit the transmission in contrast with PU activity. In this paper, we propose a method for predicting the behaviors of PU during a particular period of time. This method reflects the schedule of spectrum utilization by PU. Time information can be directed thereafter to spectrum sharing paradigms. Artificial Neural Network is used predict the channel status and provide the information to SUs control station where interference with PUs can be averted.